2005
DOI: 10.1002/marc.200400605
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State 1H NMR Studies of Degradable Poly(ethylene oxide) Based Hydrogels

Abstract: Summary: Hydrogels, the elastic chains of which are constituted of a short central poly(1,3‐dioxolane) (PDXL) block surrounded by two hydrophilic poly(ethylene oxide) (PEO) blocks, were obtained by free radical homopolymerization of α,ω–methacryloyloxy PEO‐block‐1,3‐PDXL‐block‐PEO macromonomers. The central PDXL block is known to be sensitive to acidic degradation due to the presence of acetal groups. Once swollen to equilibrium, these hydrogels were characterized for their equilibrium swelling degree and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Considering the ability of PDXL chains or PEO-block-PDXL-block-PEO copolymers [45] to undergo facile hydrolysis under acidic conditions, and the good swelling properties of PDXL based networks, applications in controlled release experiments can be foreseen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the ability of PDXL chains or PEO-block-PDXL-block-PEO copolymers [45] to undergo facile hydrolysis under acidic conditions, and the good swelling properties of PDXL based networks, applications in controlled release experiments can be foreseen.…”
Section: Resultsmentioning
confidence: 99%
“…PDXL networks or conetworks are constituted of PDXL chains sensitive to acidic media, i.e., PDXL chains, or PDXL networks degrade. [21,45] Provided poly(HEMA) could be introduced into such PXDL networks, the resulting conetworks would swell to a higher extent in water and be degradable.…”
Section: Characterization Of Swollen Pdxl-co-s or Co-bma Networkmentioning
confidence: 99%
“…Degradation of POE‐PDXL‐POE (POE, polyoxyethylene) hydrogels in water or CH 2 Cl 2 has been studied in the presence of triflic acid (pH ~ 3 in water and pH ~ 6 in CH 2 Cl 2 ) 25 . It was concluded that degradation of PDXL chains proceeds by depropagation starting from primary scission taking place anywhere in the chain, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential of these conetworks is not fully developed, since they usually contain at least one broadly distributed phase, either from the macromer/monomer approach, by free radical cross-linking of telechelic block copolymers , or random cross-linking of linear homopolymers and star-shaped homopolymers or dendrimers . Only a few examples of APCNs with only narrowly distributed segments, so-called “near perfect” or “ideal” APCNs are known, being PEG/PDMS, , the APCNs of Patrickios, who cross-links acrylate-based multiblock copolymers by group transfer polymerization , and star-shaped PIB and PEG based APCNs of Erdodi and Iván with perfect chain end coupling, or by a combination of both strategies .…”
Section: Introductionmentioning
confidence: 99%